Ethical Aspects of the Influence of Neural Networks on the Lives of Students in the Context of a Sociological Approach (using the Example of Students of the IT Department of ETU) - A. S. Kurapova; S. V. Kurapov; A. D. Derzhavina; N. V. Shatilo (Дискурс, 2025)
Introduction. The article is devoted to the analysis of the development and implementation of artificial intelligence systems, in particular neural networks, in the life of students. Their use can both open up new horizons and raise serious ethical questions, especially in the context of influencing young people and their educational trajectories. The article highlights the ambivalence of young people's perception of technology, where, on the one hand, their use arouses great enthusiasm, on the other, there is concern about the risks of manipulation and the spread of misinformation.Methodology and sources. The modern understanding of artificial intelligence as a complex of technologies capable of imitating human cognitive functions, including selflearning, is considered. The concepts of А. Toffler, M. Castells and some other researches are discussed, emphasizing the importance of information and knowledge in the process of social development and the increasing autonomy of users in the digital age. The article focuses on an interdisciplinary approach in the study of artificial intelligence. Its possibilities in the educational process based on the ethical principles of a human-oriented approach are discussed (A.V. Rezaev, N.D. Tregubov). Results and discussion. A sociological diagnosis of the students of the Faculty of Computer Technology of ETU was carried out to study the influence of neural networks on their vital decision-making. The survey covered 487 respondents. The results showed that the majority of students (59.2 %) positively assess the use of neural networks, while 85.1 % of respondents use them for educational purposes. A significant portion of the respondents expressed concerns about ethical issues related to the use of neural networks, including loss of autonomy in decision-making and lack of human interaction. The analysis of the responses of the ChatGPT-3.5 neural network to questions related to solving ethical dilemmas was carried out, which confirmed the ability of the neural network to emotionally analyze and take into account ethical aspects.Conclusion. The authors focus on the wide potential of using neural networks to make important decisions, but also emphasize the risk of losing subjectivity and increasing the importance of neural networks as a separate value for the individual. To ensure the ethical and safe use of these technologies, it is recommended to increase the transparency of algorithms, provide user training, and develop ethical standards and regulations for their use.